Social Media Marketing untuk Para Penggiat UMKM di Kecamatan Bojongloa Kidul - Foster, Bob; Rusnendar, Elan; Saberina, Sabilla (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2022)
Bojongloa Kidul District is an area that has as many as 28 MSMEs which are divided into 10 MSMEs in the field of food culinary, 6 MSMEs in hijab fashion convection, 4 MSMEs in handicrafts, 6 MSMEs in culinary and beverages and 2 MSMEs in services. However, the number of MSMEs has not been balanced with the social media-based marketing capabilities of MSME actors. The challenges faced by MSME actors are how to create interesting content and schedules that are still inconsistent. This is due to the limited ability to use social media and the use of the features of social media. In addition, MSME actors expect an increase in their ability to create content, both photos and videos of their products or services. So that social media-based marketing used by MSME actors in Bojongloa Kidul District can be more effective and efficient with training from other parties.